Preparation of carbon dot/polyaniline composites as voltage based dielectric material for capacitor applications - Cogalmis, Fatma Tuba; Demirelli, Kadir; Barim, Esra; Uk, Nida; Unlu, Caner; Senkal, Bahire Filiz; Yakuphanoğlu, Fahrettin (Elsevier, 2024)
Polyaniline-carbon dot (CD/PANI) composites were prepared via in-situ oxidative polymerization of aniline in the presence of carbon dots, with specific concentrations carefully controlled during synthesis. The composite was characterized using spectroscopic (FT-IR), morphological (TEM, SEM) and electrical methods. Impedance analysis was employed to investigate the transport behavior of charge carriers in the frequency range of 500 Hz to 10 MHz at 25 degrees C. This study provides a comprehensive analysis of the dielectric properties of the CD/PANI composite, including dielectric constant, dielectric loss, loss factor, AC conductivity, admittance, impedance, and Cole-Cole plots. The dielectric constant of the CD/PANI composite was 6.97 for 1 kHz at 0.5 V and 12.87 for 1 kHz at 5 V. The values indicate that the increase in the dielectric constant of nanocomposite with increasing voltage. This suggests that CD/PANI composite is a dielectric material whose dielectric constants are controlled by applied voltage. Notably, the dielectric constant increased with rising applied voltage and decreased with increasing frequency. Current-voltage (I-V) measurements revealed that the composite's dielectric parameters could be tuned by varying the applied DC voltage, suggesting its potential as a voltage-dependent dielectric (VDD) material for capacitor applications. Furthermore, the enhanced electrical conductivity indicates that the CD/PANI composite is a promising candidate for next-generation dielectric devices.
Keywords: Carbon dots; Polyaniline; Composite; Dielectric properties; Cole-Cole plot